Hepatoprotective Effectiveness Test of Salam Leaf Extract in Anthracyclin-Induced Rats - Hariyento Halim; Ermi Girsang; Ali Napiah Nasution (International Journal of Health and Pharmaceutical (IJHP), 2022)
Cancer is the most often diagnosed disease in the world and the top cause of death. Doxorubicin is a widely used systemic therapy, although its efficacy is limited by dose-related toxicity, including haematological suppression, organotoxicity, and hepatotoxicity. Bay leaf is a commonly utilised plant in the community for treating and preventing many diseases because it includes secondary metabolites that are antioxidants such as phenolics, alkaloids, saponins, steroids, triterpenoids, and tannins. The purpose of this work is to characterise EEDS, identify its secondary metabolite content, and test its nephroprotective effect in doxorubicin-induced rats using SGPT and SGOT levels and liver histology. This is a laboratory experimental investigation using rats and comprises of treatment groups receiving 0.5% of CMC-Na, Nature E, or EEDS at doses of 100 mg/kgBW, 300 mg/kgBW, or 500 mg/kgBW, respectively, followed by doxorubicin. The results indicated that EEDS had 21.64 % water soluble material, 1.79 % total ash, 9.98 % water, 45.38 % ethanol soluble extract, and 0.39 % acid insoluble ash. EEDS included alkaloids, flavonoids, tannins, glycosides, saponins, and steroids/triterpenoids, as determined by phytochemical screening. EEDS doses of 100 mg/kgBW, 300 mg/kgBW, and 500 mg/kgBW can significantly lower SGPT by 34%; 52,46%; 59,31% and SGOT levels by 27,05%; 43,96%; 50,07% and can improve the liver histopathology of doxorubicin-induced rats by reducing pyknotic degeneration, inflammatory cell infiltration, bleeding, steatosis and sinusoidal dilatation with an effective dose of 500 mg/kgBW with a significant difference with the doxorubicin group followed by 0.5% CMC Na. The key to bay leaf ethanol extract has hepatoprotective activity.